Two-dimensional semiconductors of Cr–X3–H3 (X = O, S, Se, and Te) structures with large magnetic anisotropy and high Curie temperature. (1st December 2022) - Moaied, Mohammed; Soliman, S
Abstract: In this study, using first-principles calculations, we predicted a novel family of two-dimensional (2D) magnetic materials: hydrogenated chromium tri-chalcogenides Cr–X3 –H3 (X = O, S, Se, and Te). Hydrogenated chromium tri-chalcogenides materials are dynamically stable and can therefore be synthesized in the laboratory. Generally, 2D Cr–X3 –H3 crystals have a semiconducting band structure, with gaps as large as 2.38 eV in the case of Cr–O3 –H3 . The Cr–O3 –H3 is the only one presenting antiferromagnetic order with out-of-plane magnetic anisotropy energy (MAE), whereas the rest (X = S, Se, and Te) are ferromagnetic with strong in-plane MAE, which increases when going down from oxygen to tellurium in the periodic table. Using Monte Carlo methods, we also obtained the Curie temperature ( T c ), which showed the expected dependence on X atoms based on the MAE values. Moreover, the Cr–X3 –H3 systems showed weakly frequency-dependent of the dielectric functions. Therefore, the refraction index variance with frequency is slight, and the reflectivity is nearly zero in all the systems. The current study is an example of how simulations can aid in the design of 2D materials that have large MAE and high T c values for next-generation spintronic devices.